Community-Based Conditional Cash Transfers in Tanzania : Results from a Randomized Trial - Evans, David K.; Hausladen, Stephanie; Kosec, Katrina; Reese, Natasha (Washington, DC: World Bank, 2014)
Given the success of conditional cash transfer (CCT) programs elsewhere, in 2010 the Government of Tanzania rolled out a pilot CCT program in three districts. Its aim was to see if, using a model relying on communities to target beneficiaries and deliver payments, the program could improve outcomes for the poor the way centrally-run CCT programs have in other contexts. The program provided cash payments to poor households, but conditioned payments on complying with certain health and education requirements. Given scarce resources, the Government randomly selected 40 out of 80 eligible villages to receive the pilot program. Households in participating and comparison villages were broadly comparable at baseline. This report describes the program and the results of a rigorous, mixed methods impact evaluation.